Cancer Crossings : A Brother, His Doctors, and the Quest for a Cure to Childhood Leukemia - Wendel, Tim (Book collections on Project MUSE., 2018)
When Eric Wendel was diagnosed with acute lymphoblastic leukemia in 1966, the survival rate was 10 percent. Today, it is 90 percent. Even as politicians call for a ""Cancer Moonshot, "" this accomplishment remains a pinnacle in cancer research. The ...